Borrelia persica Infection in Immunocompetent Mice--A New Tool to Study the Infection Kinetics In Vivo. - Sandra Schwarzer; Evelyn Overzier; Walter Hermanns; Gad Baneth; Reinhard K Straubinger (PLoS Neglected Tropical Diseases, 2016)
Borrelia persica, a bacterium transmitted by the soft tick Ornithodoros tholozani, causes tick-borne relapsing fever in humans in the Middle East, Central Asia and the Indian peninsula. Immunocompetent C3H/HeOuJ mice were infected intradermally with B. persica at varying doses: 1 x 10(6), 1 x 10(4), 1 x 10(2) and 4 x 10(0) spirochetes/mouse. Subsequently, blood samples were collected and screened for the presence of B. persica DNA. Spirochetes were detected in all mice infected with 1 x 10(6), 1 x 10(4) and 1 x 10(2) borrelia by real-time PCR targeting the flaB gene of the bacterium. Spirochetemia developed with a one- to two-day delay when 1 x 10(4) and 1 x 10(2) borrelia were inoculated. Mice injected with only four organisms were negative in all tests. No clinical signs were observed when infected mice were compared to negative control animals. Organs (heart, spleen, urinary bladder, tarsal joint, skin and brain) were tested for B. persica-specific DNA and cultured for the detection of viable spirochetes. Compiled data show that the target organs of B. persica infections are the brain and the skin. A newly developed serological two-tiered test system (ELISA and western blot) for the detection of murine IgM, IgG and IgA antibody titers against B. persica showed a vigorous antibody response of the mice during infection. In conclusion, the infection model described here for B. persica is a platform for in vivo studies to decipher the so far unexplored survival strategies of this Borrelia species.